2021
DOI: 10.3389/fcell.2021.644630
|View full text |Cite
|
Sign up to set email alerts
|

CaMKIIδ Splice Variants in the Healthy and Diseased Heart

Abstract: RNA splicing has been recognized in recent years as a pivotal player in heart development and disease. The Ca2+/calmodulin dependent protein kinase II delta (CaMKIIδ) is a multifunctional Ser/Thr kinase family and generates at least 11 different splice variants through alternative splicing. This enzyme, which belongs to the CaMKII family, is the predominant family member in the heart and functions as a messenger toward adaptive or detrimental signaling in cardiomyocytes. Classically, the nuclear CaMKIIδB and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 154 publications
0
12
0
Order By: Relevance
“…Echocardiography showed that compared with the control group, HF mice had diastolic and systolic dysfunctions, the levels of EF, FS, and E/A were decreased ( Figures 1A–C ), and the expressions of hypertrophy and HF indexes ANP and BNP were significantly increased ( Figures 1D,E ), indicating that an HF model was successfully established in this study. CaMKIIδ alternative splicing disorder easily promotes cardiomyocyte dysfunction and ultimately leads to heart disease ( 27 ). Since there is no specific antibody for CaMKIIδ splice variants, qRT-PCR was used to detect the expressions of CaMKIIδ A, CaMKIIδ B, and CaMKIIδ C at the mRNA level.…”
Section: Resultsmentioning
confidence: 99%
“…Echocardiography showed that compared with the control group, HF mice had diastolic and systolic dysfunctions, the levels of EF, FS, and E/A were decreased ( Figures 1A–C ), and the expressions of hypertrophy and HF indexes ANP and BNP were significantly increased ( Figures 1D,E ), indicating that an HF model was successfully established in this study. CaMKIIδ alternative splicing disorder easily promotes cardiomyocyte dysfunction and ultimately leads to heart disease ( 27 ). Since there is no specific antibody for CaMKIIδ splice variants, qRT-PCR was used to detect the expressions of CaMKIIδ A, CaMKIIδ B, and CaMKIIδ C at the mRNA level.…”
Section: Resultsmentioning
confidence: 99%
“…34 CaMKIIδB is mainly located in the nucleus and related to gene transcription regulation. 35 CaMKIIδC is located in the nucleus and cytoplasm and regulates cardiovascular Ca 2+ processing and contractility. 36 Research has proved that the deficiency of CaMKIIδC can reduce myocardial IR injury 33 and AngII-induced myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac-specific approaches tend to focus on the role of δ variants (reviewed by [ 17 , 24 ]), while γ variants are still relatively less studied across all tissue groups. To date, 11 splice variants of the δ isoform [ 25 ] have been described; however, the total number of γ variants identified is less clear [ 26 ]. While these studies have helped further the understanding of the splice variants, the differential expression of such variants prevents translation to a vascular context [ 17 ].…”
Section: Splicing Events In Camkiiδ and γ Isoformsmentioning
confidence: 99%
“…CaMIKIIδ9 is appreciated as the dominant splice variant in the human heart, with overexpression suppressing Ubiquitin-conjugating enzyme E2T (UBET)-dependent DNA repair, contributing to heart failure and cardiomyopathy [ 25 ]. CaMKIIδ1 (also referred to as δA) has high expression in neonates with decreased expression during adulthood, in the presence of upregulation of δ2 and δ3 expression, and δ1 expression is upregulated in chronic heart failure, with hypothesized roles in Ca 2+ handing through the regulation of L-type calcium channels [ 26 , 31 ]; thus, the distinct roles of these variants in cardiac pathology are clear.…”
Section: Splicing Events In Camkiiδ and γ Isoformsmentioning
confidence: 99%